Analisis Keamanan Kebersihan Kesehatan Karyawan terhadap Tingkat Kepuasan Konsumen - Richard Novrian (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
In the world of tourism is growing rapidly, this is what makes hotels in Jakarta make changes to attract consumers who will travel between companies. The problem that will be discussed in this thesis is how consumer satisfaction at Café Sirih Jakarta and how the influence of cleanliness and safety on consumer satisfaction at Millennium Sirih Hotel Jakarta. And the research methodology used is simple linear regression. The purpose of the results of this study is to determine the effect of hygiene and safety quality variables on consumer satisfaction, a T test was carried out.The conclusion of this study is cleanliness and safety and consumer satisfaction at Café Sirih at the millennium betel hotel Jakarta there remains the lowest dimension that needs to be improved and considered by the owner of the millennium betel hotel Jakarta and the advice from this study is on cleanliness and safety in a betel café must need to be improved again and needs to be arranged.